CBCT study of root apices distance to mandibular canal in peruvian population = Estudio de tomografía computarizada de haz cónico de las distancias de los ápices radiculares al canal mandibular en una población peruana - Manrique, Paola
The purpose of this study was to compare the average distances from the root apices of the first molars, second molars, and second premolars to the mandibular canal according to sex in the Peruvian population using cone-beam computed tomography (CBCT). Eighty CBCT scans of Peruvian patients aged from 15-80 years were examined. After locating the mandibular canal, measurements of the vertical distances from the mandibular canal to the apices of the second premolars, as well as the first molars and second molars, were made. For the statistical analysis, Student's t test was used for both paired and unpaired samples, with a significance level of p<0.05. On the right side, the second molar presented a mean distance of 3.99mm for males and 2.87mm for females, showing a significant difference (p<0.05). When compared bilaterally, no significant differences were found (p>0.05) between the distances from the apices of the second premolars and the first and second molars to the mandibular canal. However, for the second premolars and second molars on the left side, the values were higher, with averages of 5.52mm and 3.75mm, respectively.The mesial roots of the second molars were closer to the mandibular canal. In addition, women showed shorter distances than men.